2012
DOI: 10.1002/ange.201203642
|View full text |Cite
|
Sign up to set email alerts
|

A Polycomponent Metal‐Catalyzed Aliphatic, Allylic, and Benzylic Fluorination

Abstract: Große Kooperation: Die Titelreaktion mit einem Mehrkomponenten‐Katalysesystem aus dem käuflichen Selectfluor, der Radikalquelle N‐Hydroxyphthalimid, dem anionischen Phasentransferkatalysator KB(C6F5)4 und einem Kupfer(I)‐Diimin‐Komplex liefert selektiv die monofluorierten Produkte (siehe Beispiel), ohne dass ein Überschuss des Alkansubstrats eingesetzt werden müsste.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(17 citation statements)
references
References 43 publications
(32 reference statements)
0
17
0
Order By: Relevance
“…A reason may be a lack of studies of substitution reactions by radicals of high electron affinity. While the TEDA 2+• radical dication has been proposed as an intermediate in recently reported aliphatic C–H oxidation methodologies utilizing Selectfluor, 22 - 24 to our knowledge addition of this radical to unsaturated systems has not been investigated. The most commonly employed radicals in a synthetic context are uncharged carbon-, oxygen-, nitrogen-, and halogen-based radicals, which have electron affinities in the range of 0.8–3.6 eV, far below the value for TEDA 2+• (12.44 eV, Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…A reason may be a lack of studies of substitution reactions by radicals of high electron affinity. While the TEDA 2+• radical dication has been proposed as an intermediate in recently reported aliphatic C–H oxidation methodologies utilizing Selectfluor, 22 - 24 to our knowledge addition of this radical to unsaturated systems has not been investigated. The most commonly employed radicals in a synthetic context are uncharged carbon-, oxygen-, nitrogen-, and halogen-based radicals, which have electron affinities in the range of 0.8–3.6 eV, far below the value for TEDA 2+• (12.44 eV, Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the development of regioselective halogenation by C‐H activation with wide functional‐ and protecting‐group tolerance has far‐reaching consequences. To this end, manganese‐catalyzed chlorination and fluorination by Groves,9 palladium‐catalyzed iodination by Yu,10 biphasic radical‐based halogenation by Schreiner,11 and copper‐catalyzed fluorination by Lectka12 are some noteworthy recent examples.…”
Section: Introductionmentioning
confidence: 99%
“…Since Subramanian and Manzer reported the CuF 2mediated fluorination of aromatics, [6] copper-catalyzed C À F bond formation has been developed by the groups of Hartwig, Lectka, and others. [7] In contrast, for catalytic CÀF bond activation, copper has been rarely studied. Ribas and coworkers recently showed that a Cu I /Cu III redox cycle activated C À X bonds (X = halogens) using triazamacrocyclic ligand, thus indicating an oxidative addition mechanism.…”
mentioning
confidence: 99%